The Effectiveness of the Differentiated Education Strategy According to the two (Sensory-intuitive) Patterns in the Development of the Skills of Defensive Performance in the Volleyball for Students - Ali Hussein Said Al-Moussawi (Journal of Global Pharma Technology, 2018)
The progress that covered all areas including the sports field, and in many countries of the world was not coincidental, but adopted those countries many of the elements of progress, and that sport is one of the most important aspects of life and the progress of countries to build human education, physical and mental and so that sport can achieve these goals Less time using modern teaching strategies, and it is known that the skillful defense performance of the student in volleyball is related to learning within the educational institution and is a measure to evaluate the level of skill and defense performance of the learner and scientific achievement, and this investigation largely thanks to the use of the process-based Educational methods and ways and means and activities that help students so, so it could be among the reasons attributed to them this weakness in the technically gifted defensive performance is the continuation of teachers in the use of traditional teaching strategy, despite its effectiveness in certain conditions and situations. The research community determines the students of the fourth stage in the Faculty of Physical Education and Sports Sciences University of Kerbala for the academic year (2017 - 2018) and through the results reached the following conclusions:The use of a distinct learning strategy according to the two modes (sensory-sensory) has an effective effect on the development of the aerodynamic skill of the students.The results showed that there is a preference for the use of a differentiated learning strategy based on the sensory-sensory pattern.Keywords: Education strategy, (Sensory-intuitive) patterns and defensive performance.